1998
DOI: 10.1038/sj.bmt.1701269
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated bone marrow transplantation in patients with myelodysplastic syndromes and secondary acute myeloid leukemia: an EBMT survey

Abstract: Summary:The Chronic Leukemia Working Party of the EBMT has collected data on 118 patients of median age 24 years (range 0.3 to 53 years) who underwent an allogeneic bone marrow transplantation from unrelated donors for treatment of MDS or secondary AML (RA/RARS, n = 24; RAEB, n = 26; RAEB-t, n = 34; CMML, n = 12; sAML, n = 22) between 1986 and 1996. The data were reported by 49 EBMT centers. Thirtyfour of 118 patients are alive, relapse was the cause of death in 19 of 84 patients and the remaining patients die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 8 publications
(13 reference statements)
3
70
1
1
Order By: Relevance
“…9,24,[34][35][36] However, a number of recent studies of RIC allo-HSCT have shown age to not be a significant factor affecting outcome. 5,23,32,37 In this study, although an advanced recipient age of more than 50 years showed an independent correlation with poorer OS (P ¼ 0.05), the use of the HCT-CI seemed to be a much stronger predictor of post-transplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,24,[34][35][36] However, a number of recent studies of RIC allo-HSCT have shown age to not be a significant factor affecting outcome. 5,23,32,37 In this study, although an advanced recipient age of more than 50 years showed an independent correlation with poorer OS (P ¼ 0.05), the use of the HCT-CI seemed to be a much stronger predictor of post-transplant outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16] Recent literature has indicated that performance status of transplant recipients, rather than recipient age per se, may be a better indicator of the ability of a patient to tolerate allo-HSCT. The Charlson comorbidity index, adapted for HSCT, has been shown to predict NRM in patients receiving allogeneic HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] For younger patients having an HLA-matched donor, allogeneic bone marrow transplantation (BMT) provides the only potentially curative treatment with approximately 40% of treated individuals becoming long-term disease-free survivors. [5][6][7][8] Relapse after allogeneic BMT remains one of the major causes of treatment failure, and is responsible for about 50% of deaths. Only a minority of relapsed patients is cured with a second BMT, which itself results in significant morbidity and mortality.…”
mentioning
confidence: 99%
“…[2][3][4] Among patients with advanced disease (45% marrow blasts), 25-45% can be expected to survive in remission at 3 years after transplantation. [3][4][5] However, among patients with both advanced and less advanced MDS, nonrelapse mortality (NRM) has been in the range of 25-70%. 3,[5][6][7][8] Amifostine (Ethyol s ), also known as Walter Reed (WR)-2721, is a phosphorylated aminothiol compound originally developed by the WR Army Institute of Research as a potentially radioprotective agent for military personnel.…”
mentioning
confidence: 99%
“…[3][4][5] However, among patients with both advanced and less advanced MDS, nonrelapse mortality (NRM) has been in the range of 25-70%. 3,[5][6][7][8] Amifostine (Ethyol s ), also known as Walter Reed (WR)-2721, is a phosphorylated aminothiol compound originally developed by the WR Army Institute of Research as a potentially radioprotective agent for military personnel. 9 Dephosphorylation to its active form WR-1065 occurs in normal tissues, but is almost negligible in tumors.…”
mentioning
confidence: 99%